PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENINGKATAN SATURASI OKSIGEN PADA PASIEN PPOK DI RUANG IGD RSUD KABUPATEN BULELENG: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2018)
Introduction: The purpose of this study was to analyze The Effect of the Breathing Relaxion Techniques on Increasing Oxygen Saturation in COPD Patient in IGD Room of RSUD Buleleng Regency. Methods: The design research was pre-experimental with one group pre-post test design. The population used in this research were COPD patient in IGD Room of RSUD Buleleng Regency. Sample used 26 respondents who have been selected by using total sampling technique. The data from the respondents were collected using an observation sheet. This research used paired dependent t-test with significant level Î± = 0,05. Result: The data shows the average value of pre 90.19 and average value of post 93.27. The result of paired dependent test t-test p value pre and post (0,000) <Î± (0,05), meaning H0 rejected and Ha accepted. Conclutions: So it can be concluded that there is Effect of the breathing relaxion on increasing oxygen saturation in CPOD patient in IGD RSUD Buleleng Emergency. Therefore, it is expected that the patient and health workers to provide or implement deep breathing relaxion techniques in patient PPOK for saturation can be increased.